Molecular Programming Design of Glyconucleic Acid Aptamer with High Stability - Yongqi Han; Rongjun Zhang; Hong‐Liang Bao; Mei Yang; Yuan Gao; Xiaobo Gao; Ruowen Wang; Weihong Tan; Ding‐Kun Ji (Advanced Science)
Abstract Functional nucleic acids (FNAs), possessing specific biological functions beyond their informational roles, have gained widespread attention in disease therapeutics. However, their clinical application is severely limited by their low serum stability in complex physiological environments. In this work, a precise molecular programming strategy is explored to prepare glyconucleic acid aptamers (GNAAs) with high serum stability. Four glyconucleic acid modules compatible with commercial solid‐phase synthesis are designed and synthesized. Through precise molecular design, the accurate modification of four different carbohydrate ligands at specific sites of DNA aptamers is achieved. It is demonstrated that glycosylation modification can significantly increase DNA aptamers’ serum stability while maintaining their structures and high affinity. The stabilization effect is superior to that of currently commonly used commercial chemical modifications. Moreover, it is confirmed that this approach displays insignificant effects on the DNA aptamers’ tumor‐targeting ability and metabolism in vivo. This method offers a simple, economical, and efficient strategy for precise glycosylation modification of nucleic acids. This allows to prepare glycosyl functional nucleic acids with high serum stability, which can expand the application scope of functional nucleic acids and promote the practical transformation of functional nucleic acids.